Silencing SAPCD2 Represses Proliferation and Lung Metastasis of Fibrosarcoma by Activating Hippo Signaling Pathway - Zhu, Bowen; Wu, Yanqin; Niu, Lizhi; Yao, Wang; Xue, Miao; Wang, Hongyu; Yang, Jianyong; Li, Jiaping; Fan, Wenzhe (Frontiers in Oncology, 2020)
The prime issue derived from fibrosarcoma is its high metastatic potential to lung. Aberrant expression of SAPCD2 has been widely reported to be implicated in the progression and metastasis in multiple cancer types. However, the clinical significance and biological roles of SAPCD2 in fibrosarcoma remain blank. Here, we reported that SAPCD2 was remarkably elevated in fibrosarcoma tissues, and differentially upregulated in fibrosarcoma cell lines compared with that in several fibroblast primary cell lines. Kaplan-Meier survival analysis revealed that overexpression of SAPCD2 was significantly correlated with early progression and metastasis, and poor prognosis in fibrosarcoma patients. Our results further showed that silencing SAPCD2 inhibited proliferation and increased apoptosis of fibrosarcoma cells in vitro. Importantly, silencing SAPCD2 repressed lung metastasis of fibrosarcoma cells in vivo. Mechanistic investigation further demonstrated that silencing SAPCD2 inhibited proliferation and lung metastasis of fibrosarcoma cells by activating Hippo signaling pathway, as evidenced by the finding that constitutively active YAP1, YAP1-S127A, significantly reversed the inhibitory effect of SAPCD2 downregulation on colony-formation and anchorage-independent growth capability of fibrosarcoma cells, and the stimulotary effect on apoptotic ratio of fibrosarcoma cells. In conclusion, SAPCD2 promotes proliferation and lung metastasis of fibrosarcoma cells by regulating activity of Hippo signaling, which represents a potential therapeutic target against lung metastatic fibrosarcoma.